Anomalia de Pelger-Huët: um relato de caso pediátrico - Caroline Mundel; Irides Aparecida Cavalari; Ana Paula Vieira; Franciele Ani Follador; Guilherme Welter Wendt; Lirane Elize Defante Ferreto (Sociedade Brasileira de Pediatria, 2022)
The Pelger-Huët anomaly (PHA) is a benign, hereditary, usually autosomal dominant condition characterized by bilobulated or completely non-segmented granulocytes and excessive chromatin aggregation that can be mistaken for band cells. PHA is a condition still poorly investigated in the medical literature, especially in developing nations. Errors in diagnosing PHA might cause wrong interpretation of leukograms. In this case, a pediatric patient (age 6) sought medical assistance due to a fever associated with diarrhea. After complete blood cell count (CBC), which showed an important left shift, PHA was suspected. The disease was confirmed with a new CBC and then followed by the family investigation for this anomaly. The younger brother and the mother were found to have the PHA. The father and the older brother were negative for the disease, thus indicating an autosomal dominant genetic transmission.